Outpatient management of chronic heart failure - Kaldara, E.; Sanoudou, D.; Adamopoulos, S; Nanas, J.N. (Expert Opin PharmacotherExpert Opin PharmacotherExpert Opin Pharmacother, 2015)
INTRODUCTION: Heart failure (HF) treatment attracts a share of intensive research because of its poor HF prognosis. In the past decades, the prognosis of HF has improved considerably, mainly as a consequence of the progress that has been made in the pharmacological management of HF. AREAS COVERED: This article reviews the outpatient pharmacological management of chronic HF due to left ventricular systolic dysfunction and offers recommendations on the use of various drugs. In addition, the present article attempts to provide practical therapeutic algorithms based on current clinical strategies. EXPERT OPINION: Continued research directed toward identifying factors associated with high pharmacotherapy guideline adherence and understanding of variants that influence response to drugs will hopefully halt or reverse the major pathophysiological mechanisms involved in this syndrome.
Keywords: Adrenergic beta-Antagonists/therapeutic use; Angiotensin-Converting Enzyme Inhibitors/therapeutic use; Chronic Disease; Clinical Trials as Topic; Disease Management; Heart Failure/*drug therapy/etiology; Humans; Outpatients; Ventricular Dysfunction, Left/complications/drug therapy